2006
DOI: 10.1021/bi060222v
|View full text |Cite
|
Sign up to set email alerts
|

Local and Global Ligand-Induced Changes in the Structure of the GABAA Receptor

Abstract: Ligand-gated channels mediate synaptic transmission through conformational transitions triggered by the binding of neurotransmitters. These transitions are well-defined in terms of ion conductance, but their structural basis is poorly understood. To probe these changes in structure, GABA(A) receptors were expressed in Xenopus oocytes and labeled at selected sites with environment-sensitive fluorophores. With labels at two different residues in the alpha1 subunit in loop E of the GABA-binding pocket, GABA elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 45 publications
4
86
1
Order By: Relevance
“…Perhaps most interestingly, picrotoxin produced a large ⌬F at one of the labeled positions, providing strong evidence that by binding in the pore it produces global conformational change (17). A more recent study on ␣1␤2 and ␣1␤2␥2 ␥-aminobutyric acid type A receptors showed that the ⌬F magnitude monitored at two binding domain residues exhibited subunit dependence (18). The results from these two studies provide strong evidence for ligand-and subunit-specific conformational changes in the ligand binding domain.…”
Section: Tablementioning
confidence: 81%
See 1 more Smart Citation
“…Perhaps most interestingly, picrotoxin produced a large ⌬F at one of the labeled positions, providing strong evidence that by binding in the pore it produces global conformational change (17). A more recent study on ␣1␤2 and ␣1␤2␥2 ␥-aminobutyric acid type A receptors showed that the ⌬F magnitude monitored at two binding domain residues exhibited subunit dependence (18). The results from these two studies provide strong evidence for ligand-and subunit-specific conformational changes in the ligand binding domain.…”
Section: Tablementioning
confidence: 81%
“…Our aim is to investigate the conformational changes induced by agonists, antagonists, and allosteric modulators by covalently labeling different residues near the extracellular M2 boundary with the sulfhydrylreactive fluorophores, methanethiosulfonate-rhodamine (MTSR) and tetramethylrhodamine-maleimide (TMRM), and simultaneously measuring current changes and fluorescence changes (15,16). This approach has been employed so far in only a few studies on Cys loop receptors (15,17,18). A particular advantage of the GlyR is that it displays little or no desensitization thereby facilitating the quantitation of ligand-induced fluorescence spectral shifts.…”
mentioning
confidence: 99%
“…A direct ligand-fluorophore interaction cannot explain results from labeled residues in loop 2 or the pre-M1 domain as they lie well away from the ligand-binding site. Direct interactions between fluorophore and ligand are difficult to categorically rule out for the remaining labeled residues in binding loops C, D, E, and F. However, many of the sites investigated here have been studied previously in VCF studies on Cys-loop receptors and in each case a variety of criteria has been used to rule out direct ligand-induced quenching or dequenching events (16,19,21,22,27).…”
Section: Discussionmentioning
confidence: 99%
“…The excised inside-out patch procedure, which has proven to be useful for cyclic nucleotide-gated channels (Zheng and Zagotta, 2003), is less useful for channels gated by extracellular ligands and therefore has not been employed. There are also indications that covalently bound fluorophores can sense structural changes in the GABA A R that presumably originate at binding interfaces, and then propagate to a non-binding subunit that has the fluorescent label (Muroi et al 2006). Concentration-response relationships are possible when the maximal DF/F (e.g.…”
Section: Voltage-clamp Fluorometrymentioning
confidence: 99%